2017
DOI: 10.3389/fped.2017.00137
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Benefits of Applying Recent Advances in Esophageal Motility Testing in Patients with Esophageal Atresia

Abstract: Infants and children with esophageal atresia commonly present with swallowing dysfunction or dysphagia. Dysphagia can lead to a range of significant consequences such as aspiration pneumonia, malnutrition, dehydration, and food impaction. To improve oral intake, the clinical diagnosis of dysphagia in patients with esophageal atresia should focus on both the pharynx and the esophagus. To characterize the complex interactions of bolus flow and motor function between mouth, pharynx, and esophagus, a detailed unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…[5][6][7][8][9][10] Generalized automatic analysis systems for interpreting bolus transit and clearance assessed by impedance remain lacking, and there are increasing studies trying to identify applicable parameters to assist in the assessment of impedance signals in HRIM in recent years. [11][12][13][14][15][16] Our study firstly combined the signals from both manometers and impedance interpretation in HRIM by calculation of the DCI to EII ratio, which is easy to apply to all types of esophageal peristalsis and bolus clearance patterns during liquid swallow tests of HRIM. We further validated the diagnostic utility for pediatric IEM and significant body weight loss > 10% within 6 months in children.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[5][6][7][8][9][10] Generalized automatic analysis systems for interpreting bolus transit and clearance assessed by impedance remain lacking, and there are increasing studies trying to identify applicable parameters to assist in the assessment of impedance signals in HRIM in recent years. [11][12][13][14][15][16] Our study firstly combined the signals from both manometers and impedance interpretation in HRIM by calculation of the DCI to EII ratio, which is easy to apply to all types of esophageal peristalsis and bolus clearance patterns during liquid swallow tests of HRIM. We further validated the diagnostic utility for pediatric IEM and significant body weight loss > 10% within 6 months in children.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies 2,[11][12][13][14] have shown that subjects with esophageal dysmotility tend to have a low DCI and high EII; therefore, we calculated the DCI to EII (EII1000, EII1250 and EII1500) ratio of each liquid swallow as DCIIR (DCIIR1000, DCIIR1250 and DCIIR1500) in this study. The esophageal impedance integral (EII) below 1500 Ω of this wet swallow was calculated using MATLAB software (version 8.6 R2015b; MathWorks, USA).…”
Section: Hrim Study and Data Interpretationmentioning
confidence: 99%
See 2 more Smart Citations
“…The main advantage of this proposed method is no care taker and physical attention is required [3] [9]; it implements the automatic monitoring procedure very easily and effectively [10][11] using hardwares. This project considers the performance metrics such as temperature of the body, pulse rate of heart, moisture in the air and baby's movement for evaluation [2] [13]. These statistics datas are provided by devices and analyzed for further response.…”
Section: Introductionmentioning
confidence: 99%